Kasih Allah Dalam Pergumulan Iman Para Leluhur Israel: Kajian Biblis dan Makna Teologis-Spiritual Bagi Umat Kontemporer - Tjang, Yanto Sandy; Acin, Mayong Andreas; Sunarso, Alfeus (SAPA - Jurnal Kateketik dan Pastoral, 2025)
This study explores the faith journeys of Israelite ancestors: Abraham, Sarah, Isaac, Rebekah, Jacob, Leah, Rachel, and Joseph, as exemplifications of God’s active, faithful, and transformative love. Employing a qualitative-theological methodology grounded in library research, the study analyzes patterns of divine love manifested through calling, promise, testing, providence, and fulfillment within the lives of the patriarchs and matriarchs. Findings indicate that Abraham and Sarah model courage and trust amid uncertainty; Isaac safeguards the generational continuity of God’s promise; Rebekah, Leah, and Rachel highlight the proactive role of women in the divine plan; Jacob experiences faith transformation through personal and familial struggles; and Joseph illustrates God’s providential care in adversity, resulting in blessing. The study affirms that God’s love operates even within human fragility and conflict, inviting active engagement in divine purposes, and contributes to Old Testament theology while offering insights for contemporary spiritual reflection on dynamic and transformative faith.